Effect of electrode separation and electrode backscatter thickness of a parallel plate ionization chamber on the measurement of dose to tissue in beta radiation fields. (August 2022) - Rakshit, S.; Kulkarni, M.S.; Sathian, V.
Abstract: Plane parallel plate ionization chamber (PPC) is used in dosimetry especially for beta particles and low energy electron beam. The response of the PPC is affected by the electrode separation, thickness and material of backscatterer. The effect of electrode separation arises due to the well-known inscattering effect of electron which causes fluence perturbation inside the chamber cavity. The perturbation is caused due to reduced electron scattering in the chamber cavity compared to an ideal phantom material and it depends on the thickness of the cavity. Furthermore, the response of PPC also gets affected by the material behind the air cavity. Variation in the response depends on the thickness and the atomic number of the material behind collecting electrode of the PPC. The theoretical studies on the effect of collecting electrode backscatter thickness and electrode separation on the response of a PPC used as a transfer standard in ISO 6980 reference beta radiation field from 85 Kr, 90 Sr– 90 Y and 106 Ru– 106 Rh radionuclides are presented. Multi-particle transport code FLUKA is used for the studies. The Polymethyl Methacrylate (PMMA) plate having 3.5 mm thickness is found to provide full backscatter for the above beta radionuclides. It is also observed that even for a well-guarded PPC, as the chamber electrode separation increases, the measured depth dose curve deviates from the ideal depth dose curve and the effective point of measurement (EPOM) of the PPC shifts towards downward direction from chamber reference point. It is also observed that the deviation between ideal and measured depth dose curve (related to EPOM shift) depends on the cavity thickness of the PPC. In the present work, optimization of design parameters of a PPC is carried out to establish it as a transfer standard in compliance with ISO 6980 for the standardization of reference beta radiation fields from 85 Kr, 90 Sr– 90 Y and 106 Ru– 106 Rh radionuclide. Highlights: Tissue dose measurement in beta radiation field using parallel plate ionization chamber (PPC). Effect of electrode separation and backscatter thickness of PPC on beta dose measurement. Theoretical simulation of PPC in beta radiation field from 85 Kr, 90 Sr– 90 Y and 106 Ru– 106 Rh sources using FLUKA transport code. Optimization of electrode separation and electrode backscatter thickness of a PPC for beta dosimetry.